A obra de Sonia Ferrari: uma revisão narrativa de suas contribuições à terapia ocupacional - Souza, Gabriela Moreira Neves de (Universidade Federal de São Carlos, 2025)
Introduction: This study presents a narrative literature review of the work of Sonia Maria Leonardi Ferrari, an occupational therapist recognized as a reference in the field of mental health and the clinical practice of psychosis. Methodology: The narrative review is a theoretical and qualitative research method aimed at the analysis, interpretation, and critical discussion of a given topic. The bibliographic search was conducted using the curriculum published on the Lattes Platform, the SciELO and LILACS databases, as well as manual searches in major scientific journals in the field of Occupational Therapy. Inclusion criteria encompassed peer-reviewed bibliographic materials, books, and book chapters authored or co-authored by Sonia Ferrari. After identifying and selecting the material, an evidence chart was prepared, containing a synthesis and the objectives of each publication. For the synthesis of the author's professional trajectory, an interview transcript from December 2020 conducted in celebration of her 45 year career and not yet published was used. Results: A total of 15 publications produced between 1990 and 2022 were identified and detailed in terms of content and objectives. Final Considerations: Throughout her clinical trajectory, Sonia Maria Leonardi Ferrari demonstrated the potential of occupational therapy in caring for individuals experiencing severe psychological distress. Her work highlights the need for a dynamic, flexible, and person-centered approach that recognizes singularities, promotes meaning, and strengthens relationships. Ferrari’s path reveals the progressive construction of a theoretical-methodological reasoning in occupational therapy, establishing a lasting legacy for professionals and researchers.
The work of Sonia Ferrari: a narrative review of her contributions to occupational therapy
Keywords: Terapia Ocupacional; Saúde Mental; Psicanálise; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar